The effects of religion on consumer behavior: A conceptual framework and research agenda. Issue 2 (13th August 2015) - Mathras, Daniele; Cohen, Adam B.; Mandel, Naomi; Mick, David Glen
Abstract: This article provides a conceptual framework for studying the effects of religion on consumer behavior, with the goal of stimulating future research at the intersection of these two topics. We delineate religion as a multidimensional construct and propose that religion affects consumer psychology and behavior through four dimensions—beliefs, rituals, values, and community. For each dimension of religion, we offer definitions and measures, integrate previous findings from research in the psychology, consumer behavior, marketing, and religion literatures, and propose testable future research directions. With this conceptual framework and research agenda, we challenge consumer researchers to ask deeper questions about why religious affiliation and level of religiosity may be driving previously established differences in consumer behavior, and to uncover the psychological mechanisms underlying the effects. This framework complements and extends previous literature and provides a new delineated framework for considering research on the effects of religion on consumer behavior.